2022
DOI: 10.1002/cam4.5561
|View full text |Cite
|
Sign up to set email alerts
|

MFAP2, upregulated by m1A methylation, promotes colorectal cancer invasiveness via CLK3

Abstract: Background: Distant metastasis is the main cause of mortality in colorectal cancer (CRC) patients. N1-methyladenosine (m1A) is a type of epitranscriptome modification. While its regulatory effect on mRNA and its role in CRC metastasis remain unclear. Methods: The m1A methylation profile of mRNAs in CRC was revealed by m1A methylated RNA immunoprecipitation sequencing. The expression of MFAP2 in tumor tissues was measured by immunohistochemistry and then correlated with the clinical characteristics and prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We performed methylated RNA immunoprecipitation sequencing (MeRIP-seq) to explore differentially methylated peaks within mRNAs by comparing CRC samples and tumor-adjacent normal tissues, and identi ed differentially expressed mRNAs simultaneously. Micro bril-associated protein 2 (MFAP2), whose mRNA is overexpressed and m1A hypermethylated in CRC, was found to promote CRC invasion in our recent study [13].…”
Section: Introductionmentioning
confidence: 79%
“…We performed methylated RNA immunoprecipitation sequencing (MeRIP-seq) to explore differentially methylated peaks within mRNAs by comparing CRC samples and tumor-adjacent normal tissues, and identi ed differentially expressed mRNAs simultaneously. Micro bril-associated protein 2 (MFAP2), whose mRNA is overexpressed and m1A hypermethylated in CRC, was found to promote CRC invasion in our recent study [13].…”
Section: Introductionmentioning
confidence: 79%
“…Compounds 12 and 17 exhibited inhibitory activity against Clk2 with IC 50 values of 617 nM and 708 nM, as shown in Table 2 . Notably, the overexpression of Clk3 in colorectal cancer [ 55 ] and hepatocellular carcinoma [ 56 ] was previously highlighted. However, none of the tested compounds revealed any significant inhibitory activity against Clk3.…”
Section: Resultsmentioning
confidence: 99%
“…The repressive impact of m 1 A on translation is probably due to its scarcity in cytosolic mRNAs [ 17 , 59 ]. For the m 1 A eraser genes ALKBH1 and ALKBH3, it was suggested that the mRNA expression of MFAP2 and the methylation modification of m 1 A were increased in colorectal cancer when ALKBH1 was silenced [ 60 ]. The depletion of ALKBH3 enhances the decay of Aurora A mRNA and inhibits its translation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%